Single sperm karyotyping of testicular sperm in non-obstructive and obstructive azoospermia using next generation sequencing - Sumiko Sueyoshi; Akifumi Ijuin; Hiroe Ueno; Ai Miyakoshi; Haru Hamada; Misaki Toda; Naoki Tsuchiya; Miki Tanoshima; Mayuko Kurumizaka; Marina Saito; Yuki Oike; Kazumi Takeshima; et al. (PLoS ONE, 2025)
The sperm of infertile men have higher rates of chromosomal abnormalities than those of fertile men. Miscarriage rate is also higher following testicular sperm extraction combined with intracytoplasmic sperm injection (TESE-ICSI). Sperm chromosomal abnormalities are assumed to be the cause of miscarriages. Previous testicular sperm karyotyping studies have only examined a few selected chromosomes using fluorescence in situ hybridization. The aim of this study was to provide a more detailed analysis of sperm karyotyping by analyzing all chromosomes using next-generation sequencing (NGS) in clinically usable testicular sperm. Sperm discarded after clinical use was collected for NGS. Additionally, sperm were individually collected by micromanipulation from patients with obstructive azoospermia (OA) and non-obstructive azoospermia (NOA) who underwent TESE-ICSI. For comparison, ejaculated sperm from control and balanced translocation (BT) carriers were examined. Karyotyping was performed on individual sperm cells using NGS. The number of normal and aberrant sperm was compared. Seventeen patients participated in this study: control (n = 4), BT (n = 3), OA (n = 5), and NOA (n = 5). Ten sperm samples per patient were analyzed. The total acquisition rate for single sperm karyotyping was 85% (145/170). Karyotyping of sperm from the BT group revealed sperm with unbalanced chromosomes derived from carrier translocations. Among the NOA group, 7/41 (17%) sperm samples exhibited aberrant karyotypes, whereas no aberrant sperm were identified in the control and OA groups. Individual differences were observed in the frequency of sperm chromosomal abnormalities among patients with NOA. In conclusion, sperm chromosomal abnormalities are frequently observed in patients with NOA even after sperm selection for clinical use. As the frequency of chromosomal abnormalities varies among patients with NOA, single sperm sequencing may help identify patients with NOA most likely to benefit from PGT-A.